Effect of Explicit Communication Strategy Instruction on EFL Students’ Speaking Self-efficacy and Speaking Performance Based on Debate Technique: Grade 11 in Focus - Nemera, Temesgen (Ethiopian Journal of Education Studies, 2025)
The purpose of this paper was to investigate if explicit communication strategy has any significant effect on EFL Grade 11Students’ speaking efficacy and speaking performance based on debate technique. The study used Quasi-experimental research design that employed quantitative research approach with research instruments namely questionnaire and rubric scores. The participants of the study were Grade 11 Natural Science Students at Wallaggaa University Boarding Special Secondary School. The setting and participants were chosen based on purposive sampling technique. The existing two intact classrooms of Grade 11 were assigned to control group ( N=35) and experimental group (N=35) using random sampling technique. The participants in both control group and experimental group were administered Questionnaire with 4 point scale that consists 12 items to make students forward views on their self-efficacy in pretest and posttest. Besides, a rubric score with 5 point scale ratingscale that contains 8 categories that consists of 36 items upon which students speaking performance was assed by raters was used. These aspects of speaking performance are vocabulary, pronunciation, grammar, fluency, comprehension, message delivery ,content, organization .Based on preliminary issues _ for reliability test, Cranach’s alpha was considered in both pretest and post test. for questionnaire ,and Pearson correlation was used for rating scale of rubric score .To this effect an statistical test independent sample t-test ANCOVA and MANOVA were employed and the result self-efficacy questionnaire obtained using descriptive statistics was (M = 3.2738, SD =0.11356) of the control group and (M =3.3800, SD = 0.25414 of the experimental group) in the post test. Inferentially, the result of the computed t-test was found to be (t (68) = 2.257, p = 0.027). As the P value is < 0.05, there was statistically a significance difference between the two groups, the value of experimental being greater than that of control group in the posttest. of sel-efficacy. In addition, values of aspects of speaking performance were computed as (Lambda (8, 61) = 0.403, p = .000). As p (.000)<the critical cut off point (0.05), statistically a significance difference was observed which could became in coincidence with results obtained from all independent sample t-tests.. Partial Eta squared with value 0.597 (which is almost .600 implies the difference between control group and experimental group to be big.Thus, it was recommended that the intervention of communication strategy instruction be taken into consideration to enhance EFL Special Secondary school students “ speaking performance thereby enhancing self-efficacy